Effects of Varying Transmitter Half Power Angle in Visible Light Communication - Kolawole, S. F.; Hamza, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Visible light communication (VLC) involves sending and receiving information using light as carrier to transmit the information from sender to receiver. One of the most important parameters of a transmitter in a VLC system is the semi angle at half power which is also referred to as the transmitter half power angle. Varying it could affect the amount of light or optical power received at the receiver and depending on the configuration of the transmitters. This can lead to loss of some part of received power. This work investigates how such variation in half power angle can affect average received power by considering separate transmitter arrangements/configuration that can be adopted for VLC based on same number of these transmitters. Six separate arrangements of six transmitters were considered in a line of sight (LoS) indoor VLC scenario. The results were achieved by varying the half power angle between a minimum of 10° and a maximum of 80°. The result showed that different levels of received power were attained at different half power angles for each different transmitter configuration. For instance at a low angle of 10^o, the third configuration had an average received power of 2.8139mW while fourth configuration had an average received power of 2.6700mW which implies the third configuration has a better performance. At a high angle of 80°, average received power for third configuration was 1.2207mW and it was 1.0672mW for the fourth configuration showing that the third configuration still performs better. The third configuration generally outperformed all the other ones. The fifth configuration had a good average received (2.8120mW) at low angle of 10^0 but it gradually became poorer (1.1782mW) at higher angles of up to 80° in comparison to other configurations which indicates this configuration does not perform well at higher half power angles. The findings of the work signified that changing the transmitter configuration can cater for power losses that maybe encountered as a result of varying the transmitter half power angle in a VLC system without giving up so much on uniformity of distribution of the light.